استغلال الوظيفة للكسب غير المشروع : دراسة مقارنة بين الفقه الإسلامي والقانون الجنائي الإندونيسي - إسمنتو، رينو (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study aims to discuss the concept of abuse of occupation in illegal earning and its forms, elements and penalties in Indonesian Criminal Law by referring to Law No. 31 of 1999 (as amended by Law No. 20 of 2001) and mentioning the views of law scholars on these matters. The study also discusses the abuse of occupation and its forms and penalties under Islamic Jurisprudence and compares Islamic Jurisprudence with Indonesian Criminal Law based on the same matters. The study used the inductive analytical approach to analyze the views of jurists and their evidence. The study discovers the following results: both Islamic Law and Indonesian Criminal Law prohibit the abuse of occupation in illegal earning. Furthermore, the study found that the stated penalties in Indonesian Criminal Law for these crimes are classified as punitive penalties as are they under Islamic Jurisprudence. It also found that if the penalties are applied properly, they can deter people from committing these crimes